Rampion—Campanula rapunculus L. - James M. Stephens (EDIS, 2003)
This document describes rampion (Campanula rapunculus L.), a biennial plant cultivated as an annual vegetable for its edible leaves and roots. Once widely used in Britain and now occasionally grown in Florida, rampion is also found in Europe, Asia, and Africa. The plant features long-oval leaves and slender white roots with a sweet, nutty flavor. It can be consumed raw or cooked. Cultivation practices are similar to radishes, with optimal sowing in Florida from September through March, though early fall plantings in Gainesville have shown poor results. Original publication date May 1994.